Tracheostomy in stroke patients - Bösel, Julian (Current treatment options in neurology, 2014)
Patients with severe ischemic and hemorrhagic stroke may require tracheostomy in the course of their disease. This may apply to stroke unit patients whose deficits include a severe dysphagia posing such risk of aspiration as it cannot be sufficiently counteracted by tube feeding and swallowing therapy alone. More often, however, tracheostomy is performed in stroke patients so severely afflicted that they require intensive care unit treatment and mechanical ventilation. In these, long-term ventilation and prolonged insufficient airway protection are the main indications for tracheostomy. Accepted advantages are less pharyngeal and laryngeal lesions than with prolonged orotracheal intubation, better oral hygiene and nursing care, and higher patient comfort. Optimal timing of tracheostomy is unclear, in general, as in stroke intensive care unit patients. Potential benefits of early tracheostomy concerning ventilation duration and length of stay, respirator weaning, airway safety, rate of pneumonia, and other complications, outcome and mortality have been suggested in studies on non-neurologic subgroups of critical care patients. Stroke patients have hardly been investigated with regard to these aspects, and mainly retrospectively. A single randomized pilot trial on early tracheostomy in 60 ventilated patients with severe hemorrhagic and ischemic stroke demonstrated feasibility, safety, and less need of sedation. Regarding the technique, bedside percutaneous dilational tracheostomy should be preferred over surgical tracheostomy because of several reported advantages. As the procedural risk is low and early tracheostomy does not seem to worsen the clinical course of the ventilated stroke patient, it is reasonable to assess the need of further ventilation at the end of the first week of intensive care and proceed to tracheostomy if extubation is not feasible. Reliable prediction of prolonged ventilation need and outcome benefits of early tracheostomy, however, await further clarification. Decannulation of stroke patients after discontinued ventilation has to follow reliable confirmation of swallowing ability, as by endoscopy.
Published online: 21 December 2013
Gesehen am 03.11.2020